An enhanced correlation for gas-particle heat and mass transfer in packed and fluidized bed reactors - Zhu, Li-Tao; Liu, Yuan-Xing; Luo, Zheng-Hong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
[Display omitted] •A Nusselt correlation for gas-particle transfer in packed bed and fluidized bed.•Particle-resolved data points (ε = [0.35, 1], Rep = [0, 550]) from open sources.•To validate the Nusselt correlation.•The correlation integrated with a macroscopic CFD reactor model. Particle-resolved (PR) high-fidelity simulations, e.g., direct numerical simulation (DNS), have emerged as a powerful tool to precisely capture the full details of complex fluid-particle heat and mass transfer behaviors. The captured information can be used to constitute closures for unresolved conservation equations. However, such simulations are commonly performed under a specific variety of operating conditions. To broaden the range of closure model applicability, this fundamental study develops an enhanced correlation for the gas-particle transport rate in terms of Nusselt (Sherwood) number via collecting data points (ε = [0.35, 1], Rep = [0, 550]) from open sources. The collected data are predicted with a mean relative error of 9.3%. The extended correlation is then systematically validated by comparison with experimental data and PR-DNS results. Finally, the correlation is applied to integrate with a macroscopic computational fluid dynamics (CFD) reactor model. Validation results reveal an enhanced improvement in mass and heat transfer predictions. Moreover, the overall thermal and reactive behaviors computed from the coupled reactor model achieve reasonably good accordance with PR-DNS predictions over various process conditions. The developed correlation is hopeful to improve the accuracy of coarse-grained simulation of interphase heat and mass transfer accompanied by heterogeneously catalyzed chemical reaction.